Medicinal Plants Used by Traditional Healers in Algeria: A Multiregional Ethnobotanical Study - Belhouala, Khadidja; Benarba, Bachir (Frontiers in Pharmacology, 2021)
Traditional medicine is the cornerstone that boosts scientific research to explore new therapeutic approaches. The study aimed to assess the traditional knowledge and use of medicinal plants to treat various ailments by Algerian traditional healers. Forty traditional healers were face to face interviewed in three different Algerian areas (West, Kabylia and Sahara). The data collected were analysed using quantitative indices such as fidelity level (FL) and Informant consensus factor (FIC). A total of 167 species belonging to 70 families were recorded. Lamiaceae (13%), Asteraceae (13%), Apiaceae (7%), Rosaceae and Fabaceae (5 % each) were the most cited families. The survey revealed that leaves were the most used parts of the plants (29%). Furthermore, decoction (35%), raw (24%), and infusion (19%) were the common modes for the remedies’ preparation. Here, 15% of the total species were newly reported as medicinal plants. Besides, it was reported for the first time a total of 47 new therapeutic uses for 20 known plant species. Of 17 ailments categories, cancer was presented by 44 species, showing the highest FIC of 0.46. Marrubium vulgare L., Artemisia herba-alba Asso., Zingiber officinale Roscoe., and Juniperus phoenicia L. recorded the maximum fidelity value of 100%. Therefore, our study reveals a strong ethnomedicinal knowledge shared by local populations living in the three regions studied. The medicinal species with high fidelity level could be promising candidates for identifying new bioactive molecules.